Tailoring Vacuum Artificial Muscles: A Multi-Parametric FEA-Driven Optimization and Monolithic Fabrication - Galassi, Laura; Lorenzon, Lucrezia; Pagliarani, Niccolo; Sarti, Alberto; Cianchetti, Matteo (IEEE robotics and automation letters, 2026)
Vacuum-actuated muscle-inspired pneumatic structures (VAMPs) are a promising alternative to traditional pneumatic artificial muscles, offering uniform force distribution, reduced material fatigue, and improved reliability through the use of negative pressure; however, their design-performance relationship remains poorly understood, and current multi-step fabrication methods limit precision and complexity. To overcome these challenges, we developed a multi-parametric finite element analysis (FEA) framework exploring 100 parameter combinations to optimize axial strain, enabling application-specific actuator designs based on geometry, size, and contraction capacity. We also propose a cost-effective monolithic fabrication process that eliminates multi-step casting and allows for complex 3D structures. Validated by pressure-strain experiments with only 4% error, our approach achieves a 21% strain improvement over state-of-the-art VAMPs, broadening their potential in wearable robotics and biomedical applications.